KANDUNGAN FLUORIDE DALAM AIR MINUM ISI ULANG DI KOTA BATAM - Nurlinda Ayu Triwuri; - Hazimah (JURNAL REKAYASA SISTEM INDUSTRI, 2018)
Water needs are very good for humans because they are human body-forming substances. Public awareness of getting water that meets health requirements is increasing. People tend to choose more practical methods with relatively low costs in meeting drinking water needs, especially in the city of Batam. One of the fulfillment of drinking water needs that is an alternative is to use refill drinking water. The source of raw water for drinking water in the city of Batam comes from reservoir water. Water is a source of high fluoride intake. Thus, fluoride levels in water used for consumption must be considered so as not to overdo it. Fluoride is a highly reactive halogen, so it is always obtained in the form of compounds. Inorganic fluorides are toxic and more irritant than organic ones. Chronic poisoning causes people to become thin, disrupted body growth, dental fluorosis and skeletal and digestive disorders that can be accompanied by dehydration. The method used in this study is simple randomized sampling. The standard method of analysis for fluoride parameters (F) is the 4500-F-D method (SPADNS colorimetric method) used in the laboratory of PT. Sucofindo Batam. Laboratory test results of PT. Sucofindo Batam from the six refill drinking water samples taken, namely Fun Qua Batu Ampar, Salsabila Batam Center, Pak De Qua Tiban, Fresh Qua, Bengkong and Salwa Qua Tembesi obtained results of fluoride level analysis of <0.06 mg / L. While the results of fluoride level analysis from Alam Qua Piayu were obtained at 0.43 mg / L. Refill water treatment from 6 locations of drinking water depots based on by Regulation of the Minister of Health No. 492 of 2010 still meets the quality standards set at 1.5 mg / L.